1999
DOI: 10.2307/2673184
|View full text |Cite
|
Sign up to set email alerts
|

Educational Expectations of Asian American Youths: Determinants and Ethnic Differences

Abstract: This paper tests three explanations for the high educational expectations of Asian-American high school students living in the United States: favorable socioeconomic and background characteristics, demonstrated academic ability, and cultural values conducive to education. We focus on differences in the relevance of these explanations across Asian-American ethnic groups. With data from the National Educational Longitudinal Study (NELS), 1988-1992, we employ five multivariate regression models to explain differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
310
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 363 publications
(339 citation statements)
references
References 28 publications
19
310
3
3
Order By: Relevance
“…Relative to whites, their parents tend to be better educated, and they are more likely to live in stable, two-parent families with higher incomes (5). This explanation, however, is insufficient because advantages in socio-demographic factors only partially explain the achievement gap (2,3,5). Moreover, Asian Americans are not uniformly advantaged in terms of family socioeconomic background.…”
Section: Explaining the Asian-american Advantage In Educationmentioning
confidence: 88%
See 2 more Smart Citations
“…Relative to whites, their parents tend to be better educated, and they are more likely to live in stable, two-parent families with higher incomes (5). This explanation, however, is insufficient because advantages in socio-demographic factors only partially explain the achievement gap (2,3,5). Moreover, Asian Americans are not uniformly advantaged in terms of family socioeconomic background.…”
Section: Explaining the Asian-american Advantage In Educationmentioning
confidence: 88%
“…These arguments, however, have been rejected by other scholars who find little difference in general intelligence between native Chinese/ Japanese children and white American children (12)(13)(14)(15). Most researchers instead attribute observed racial differences in measured cognitive ability to variations in parents' socio-economic status, parental expectations, and access to educational resources at home and in communities (2)(3)(4)(13)(14)(15).…”
Section: Explaining the Asian-american Advantage In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there is nontrivial variability in educational expectations and attainment of Asian Americans based upon national origin (see, e.g., Sakamoto, Goyette, & Kim, 2009). Goyette and Xie (1999) reported that the expectation of graduation from college is almost 30%…”
Section: Resultsmentioning
confidence: 99%
“…It seems that the very high levels of encouragement ("the most important thing to do after high school is to go to college") accounts for a share of the Asian American edge. There is a considerable literature on the very high levels of Asian American parental expectations for their children's educational attainments (Hao andBonstead-Bruns 1998, Goyette andXie 1999) But the difference between Asian American students and white students widens in Model 4 when childrearing patterns are included and in Model 5 when self-esteem and locus of control are added as covariates. The reason is that Asian American families (especially VCL Asian Americans) are less likely to communicate with their children and are more likely to try to control them.…”
Section: Table 5 About Herementioning
confidence: 99%